Amniotic fluid stem cell‐derived extracellular vesicles are independent metabolic units capable of modulating inflammasome activation in THP‐1 cells. Issue 4 (26th February 2022) - Mezzasoma, Letizia; Bellezza, Ilaria; Orvietani, Pierluigi; Manni, Giorgia; Gargaro, Marco; Sagini, Krizia; Llorente, Alicia; Scarpelli, Paolo; Pascucci, Luisa; Cellini, Barbara; Talesa, Vincenzo Nicola; Fallarino, Francesca; et al.
Abstract: An immunoregulatory role of stem cells, often mediated by their secretome, has been claimed by several studies. Stem cell‐derived extracellular vesicles (EVs) are crucial components of the secretome. EVs, a heterogeneous group of membranous vesicles released by many cell types into the extracellular space, are now considered as an additional mechanism for intercellular communication. In this study, we aimed at investigating whether human amniotic stem cell‐derived extracellular vesicles (HASC‐EVs) were able to interfere with inflammasome activation in the THP‐1 cell line. Two subsets of HASC‐EVs were collected by sequential centrifugation, namely HASC‐P10 and HASC‐P100. We demonstrated that HASC‐EVs were neither internalized into nor undertake a direct interaction with THP‐1 cells. We showed that HASC‐P10 and P100 were able to intrinsically produce ATP, which was further converted to adenosine by 5'‐nucleotidase (CD73) and ectonucleoside triphosphate diphosphohydrolase‐1 (CD39). We found that THP‐1 cells conditioned with both types of HASC‐EVs failed to activate the NLRP3/caspase‐1/inflammasome platform in response to LPS and ATP treatment by a mechanism involving A2a adenosine receptor activation. These results support a role for HASC‐EVs as independent metabolic units capable of modifying the cellular functions, leading to anti‐inflammatory effects in monocytic cells.